PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XII IPA MAN 2 KOTA PADANG - Putri, Niken Asrina (Jurnal Edukasi dan Penelitian Matematika, 2023)
One of the important abilities that students must have is mathematical communication skills. However, because the leairning model used in class XII IPA MAN 2 Padang City still focuses on the teacher does not support the development of students' mathematical comunication skill, students' mathematical communication abilities are considered low. Modelproblem based learning (PBL) is used to overcome this problem. Theaim of the research is to explain how students learn mathematical comunication by applying the problem basedd leairning (PBL) model and to analyze the differences in students' mathematical comunication using the PBL model which is better than the direct leairning model. Types of research quasi-experimental research (quasy experiment) with plans nonequivalent postest-only control group design, and descriptive research. The research population is student of class XII IPA MAN 2 Padang City for the 2023/2024 academic year. Sampling methodsimple random sampling with class XII Science 6 experimental groups and XII Science 4 control classes. The research instrument uses quizzes and final tests. Basedd on the results of the quiz analysis, it was found that, for each indicator, except indicator 2, mathematical communication skills had increased, and basedd on the results of hypotesis testing with a level of 0.05, it was obtained, meaning  until minus . This shows that the mathematical communication skill of students who study with the PBL model are better than those who study with the direct leairning model. In this way, it was conclud that therewas an influeince of the PBL model on the mathematical communication skills of students in class XII IPA MAN 2 Padang City..Keywords- Problem Based Learning Models, Comunication Mathematical Ability, Direct Learning Models.